Development of tools to automate quantitative analysis of radiation damage in SAXS experiments. (24th November 2016) - Brooks-Bartlett, Jonathan C.; Batters, Rebecca A.; Bury, Charles S.; Lowe, Edward D.; Ginn, Helen Mary; Round, Adam; Garman, Elspeth F.
Abstract : Radiation damage analysis with experimental SAXS data allows for the quantitative comparison of the efficacy of various additive radioprotectant compounds. Relevant extensions to RADDOSE‐3D and the creation of a new visualization library to enable this study are presented. Abstract : Biological small‐angle X‐ray scattering (SAXS) is an increasingly popular technique used to obtain nanoscale structural information on macromolecules in solution. However, radiation damage to the samples limits the amount of useful data that can be collected from a single sample. In contrast to the extensive analytical resources available for macromolecular crystallography (MX), there are relatively few tools to quantitate radiation damage for SAXS, some of which require a significant level of manual characterization, with the potential of leading to conflicting results from different studies. Here, computational tools have been developed to automate and standardize radiation damage analysis for SAXS data. RADDOSE‐3D, a dose calculation software utility originally written for MX experiments, has been extended to account for the cylindrical geometry of the capillary tube, the liquid composition of the sample and the attenuation of the beam by the capillary material to allow doses to be calculated for many SAXS experiments. Furthermore, a library has been written to visualize and explore the pairwise similarity of frames. The calculated dose for the frame at which three subsequent frames are determined to be dissimilar is defined as the radiation damage onset threshold (RDOT). Analysis of RDOTs has been used to compare the efficacy of radioprotectant compounds to extend the useful lifetime of SAXS samples. Comparison of the RDOTs shows that, for radioprotectant compounds at 5 and 10 m M concentration, glycerol is the most effective compound. However, at 1 and 2 m M concentrations, dithiothreitol (DTT) appears to be most effective. Our newly developed visualization library contains methods that highlight the unusual radiation damage results given by SAXS data collected using higher concentrations of DTT: these observations should pave the way to the development of more sophisticated frame merging strategies.